A Novel Ber Analysis Approach For Different Modulation Schemes For Conventional And Wavelet Based Ofdm System (International Journal of Engineering and Computer Science, 2015)
Orthogonal Frequency Division Multiplexing is considered as an advanced communication model which has wide range of applications such as 3G, 4G, and Wi-Fi etc. Comparing with Frequency Division Multiplexing (FDM), we are providing a higher level of spectral efficiency by using the OFDM Multiple Carriers. To overcome the problems of the Inter carrier interference (ICI) and inter symbol interference (ISI), using of the cyclic prefix which uses the available bandwidth of 20% for the loss of the Orthogonality between the sub carriers in OFDM. Providing of better Orthogonality which is based on the wavelet of OFDM and improving of BER (Bit Error Rate) is also used in it. Increasing of the spectral efficiency we doesn’t require the cyclic prefix which is based on the wavelet system. In the upcoming of the 4th generation LTE, using of wavelets in place of Discrete Fourier Transform (DFT) based OFDM is proposed. Using of the wavelets and DFT based OFDM Systems we have compared the performance of the BER.